Discussions on inclusion in times of biopolitics and neoliberalism - João Paulo Risso; Thiago Donda Rodrigues; Fernanda Malinosky Coelho da Rosa (Prometeica, 2023)
This article aims to bring a discussion about inclusion in times of biopolitics and neoliberalism and, for that, we will present concepts and understandings about normalization, medicalization, and neoliberalism. In the search for an analytical movement and using the methodology of bibliographic research, we selected three academic works defended by the GEduMaD research group and we read them from the theoretical lens presented at the beginning of the text.